Francisco Sionil Jose: A Multicritique On his Select Short Fictions - Desales, Ma. Asuncion (JPAIR Multidisciplinary Research, 2019)
Genres of literature depict ideas and feelings which are universally felt by everyone, therefore, reading them by heart and comprehending them deeply lead the readers to have wider horizons and understanding of the different cultures of people. This study scrutinizes the textuality of Jose’s three short fictions titled: The God Stealer, The Refugee, and The Forest through a dimensional critique. It used the different critical theories of literature such as mimetic, expressivist, formalistic, and affective. Through analysis, a reader is encouraged to envision and reflect on his real-life situation. The findings conclude that the short fictions of Jose are exemplary and should be meticulously ready and studied since they contribute lots of knowledge in understanding oneself and the world he lives in. Also, this study recommends every student develop a passion for reading and get acquainted with the different theories of literature, fully understand the meaning of each story, and build a strong and better understanding of the perplexing events happening these days. Consequently, the multi critique applied to the fiction helped students to comprehend each selection well, so with the supervision of the researcher her students were able to develop translational outputs namely one-act-play, soliloquy, spoken poetry, storytelling, poem, and dance drama.